Usando o luxo, consumindo o espaço: uma investigação sobre as relações entre espaço, consumo de moda e luxo - Maldonado, Maura Carneiro (2009)
Luxury consumption in Brazil has been growing significantly, this country being considered one of the 10 largest luxury markets in the world.Though it is restricted to just 1% of the population, the sector already sets in movement US$2,5 billion per year. This strong commercial presence stimulates theoretical and academic analysis about the theme. Some studies were developed in the sense of shedding light on the behaviour f luxury consumers and the symbolic aspects associated to it. However, the proposal of this dissertation is to review the relations between the consumption of luxury fashion and the space thereby occupied. The main assumption is that there is an exchange between the meanings of this type of consumption, its potential consumers and the marketplace where these elements complete one another and are realized in the social field. The research was made through an ethnographic qualitative investigation with two main sources of data: in-depth interviews and participant observation and the exam of information was made through discourse analysis. The motivations for luxury consumption were identified as the quality of products in themselves, the beauty and distinction attached to it and the hedonism in the differentiated experience of acquisition. As to space, the analysis of the data demonstrate that high prestige shops follow spatial codes and references consciously or unconsciously developed by high acquisition groups. The placing of this type of establishment must be in harmony with the aspects of luxury products, being also a reflex of those. It is important that there exists an identification between the offered product, the shopping point and the identity of the consumers. The symbolic aspects of space turn to the perception of the product, thereby having the power to highlight its qualities, as well as it may bring about a negative view of the products, as a consequence of the lowering of the values connected to it such as authenticity, beauty, status and prestige amongst others.